2022
DOI: 10.3390/agronomy12061418
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of RAZORMIN® as a Biostimulant and Its Effect on the Phytotoxicity Mitigation Caused by Fungicide Azoxystrobin in Pepper

Abstract: Use of biostimulants for stimulating plant growth and mitigating the negative impacts of biotic and abiotic stresses is a promising strategy to achieve higher crop yields. Fungicides such as azoxystrobin are used to control several pests and fungal diseases in plants but at the cost of altering various physiological processes; thereby, leading to reduced crop yields. The efficiency of the compound RAZORMIN® as a biostimulant product while taking into account its role in plant growth stimulation and fungicide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 70 publications
1
0
0
Order By: Relevance
“…Chitinases play important role in the production of carbon and nitrogen. It increases the plant growth by improving nitrogen metabolism, sugar content, fresh weight and photosynthetic activity (Ahmad et al, 2022). Current study is supported by Kolomiiets et al (2017a) who used pyraclostrobin against Cmm and P. syringae pv.…”
Section: Discussionsupporting
confidence: 63%
“…Chitinases play important role in the production of carbon and nitrogen. It increases the plant growth by improving nitrogen metabolism, sugar content, fresh weight and photosynthetic activity (Ahmad et al, 2022). Current study is supported by Kolomiiets et al (2017a) who used pyraclostrobin against Cmm and P. syringae pv.…”
Section: Discussionsupporting
confidence: 63%
“…These findings agree with those obtained by Ávila-Pozo et al [5], who examined the effects of applying the same biostimulant (also through root and foliar application) to tomato crops. Para diković et al [6,18] and Ahmad et al [11] also observed elevated concentrations of photosynthetic pigments in pepper plants treated with various biostimulants composed of amino acids and organic matter. These authors suggest that the increased content of photosynthetic pigments is a result of enhanced nitrogen (N) absorption by the plant.…”
Section: Discussionmentioning
confidence: 94%
“…In our experiment, the application of the biostimulant notably improved the mineral nutrition of bell pepper crops. Adequate crop mineral nutrition is essential for optimal plant growth and development [11]. Both macro-and micronutrients play essential roles in regulating various physiological processes and facilitating metabolic reactions, including photosynthesis and nitrogen assimilation, while also serving as precursors or activators of various enzyme systems [11,31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation